Investigating the Linguistic and Pedagogical Barriers to English Language Learning among Kannada Learners at Govinda Pai Memorial Government College - AL Muneera J.; Sujish S., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
The multicultural and multilingual landscape of Kasaragod district in Kerala offers a unique context for English language learning among Kannada-speaking students. This study examines the intersection of linguistic identity, cultural plurality, and student engagement in English classrooms at Govinda Pai Memorial Government College, Kasaragod. It explores how the multicultural identity of Kannada-background learners shapes their learning experiences, influences pedagogical strategies, and contributes to a broader understanding of inclusive education in linguistically diverse settings. Drawing from classroom observations, institutional experiences, and a review of relevant literature, the paper highlights the significance of culturally responsive pedagogy and learner-centered practices in promoting engagement and proficiency in English. The findings underscore that English language teaching in multilingual environments must move beyond linguistic competence to embrace cultural sensitivity, identity affirmation, and reflective pedagogy.
Keywords: Multicultural identity; Kannada students; English language learning; student engagement; pedagogy; bilingualism